UNCED: No consensus on combating the greenhouse effect? - Harald Sondhof (Intereconomics, 1992)
Concrete steps aimed at combating global warming (or the “greenhouse effect”) are intended to be decided at the United Nations Conference on Environment and Development, which is to be held in Rio de Janeiro in June 1992. So far, it has not proved possible to reach a consensus on several decisive questions. The final meeting of the Preparatory Committee in March offers the last chance of achieving a rapprochement.
Keywords: 330; Environment